2018
DOI: 10.1029/2017rs006428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electric Field and Neutral Wind on the Asymmetry of Equatorial Ionization Anomaly

Abstract: The zonal electric field and the meridional neutral wind are the principal drivers that define the geometry and characteristics of the equatorial ionization anomaly (EIA). Here we present the response of the EIA to the variability of the zonal electric field based on measurements of the equatorial electrojet (EEJ) currents and trans‐equatorial neutral winds for the generation and control of the asymmetries of the EIA crests of total electron content (TEC) in the western side of the South American continent. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 54 publications
4
67
0
Order By: Relevance
“…It has been shown that the effects of perturbation meridional winds could reach to equatorial latitudes only after 20-24 hr of the commencement of the MP (Bauske & Prölss, 1997;Fuller-Rowell et al, 2002;Prölss, 1995). Thus, this storm provides clear evidence that PPEF alone can be sufficient to modulate TEC over low latitudes in episodic manner supported by background meridional winds (Khadka et al, 2018). Thus, this storm provides clear evidence that PPEF alone can be sufficient to modulate TEC over low latitudes in episodic manner supported by background meridional winds (Khadka et al, 2018).…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 76%
See 4 more Smart Citations
“…It has been shown that the effects of perturbation meridional winds could reach to equatorial latitudes only after 20-24 hr of the commencement of the MP (Bauske & Prölss, 1997;Fuller-Rowell et al, 2002;Prölss, 1995). Thus, this storm provides clear evidence that PPEF alone can be sufficient to modulate TEC over low latitudes in episodic manner supported by background meridional winds (Khadka et al, 2018). Thus, this storm provides clear evidence that PPEF alone can be sufficient to modulate TEC over low latitudes in episodic manner supported by background meridional winds (Khadka et al, 2018).…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 76%
“…Emphasizing the competing roles of meridional neutral winds and vertical E × B drifts during quiet time, Khadka et al (2018) have recently explained the asymmetry in EIA due to the presence of interhemispheric meridional under strong or weak E × B drift. In case if there were no background meridional winds the equatorial plasma fountain formed due to vertical E × B drift shall almost equally distribute the plasma in low-latitude regions in both the hemispheres.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations